Excess Conductivity Analyses in Bi-Pb-Sr-Ca-Cu-O Systems Sintered at Different Temperatures - Dung, Tran Tien; An, Pham The; Duong, Tran Ba; Man, Nguyen Khac; Thi Minh Hien, Nguyen; Hai Duc, Tran (VNU Journal of Science: Mathematics - Physics, 2021)
This paper studies the effects of the sintering temperature on crystal structure, critical temperature (T c ) and excess conductivity of Bi-Pb-Sr-Ca-Cu-O (BPSCCO) system. Bulk BPSCCO samples were fabricated by the solid-state reaction method. Four different temperatures of 835 °C, 840 °C, 845 °C, and 850 °C were applied to sinter four different samples. The crystal structure of the samples was investigated through X-ray diffraction measurements (XRD) and scanning electron microscopy (SEM). Superconductivity of the samples was analyzed by the temperature-dependent resistivity measurement. The experimental results showed the existence of both Bi-2223 and Bi-2212 phases in all samples. Quantitatively, the volume fraction of the Bi-2223 phase was found to increase from 53.56% to 75.97%, and the average grain size of Bi-2223 phase was observed to enlarge from 57.95 nm to 86.50 nm as the sintering temperature increased from 835 °C to 850 °C. In addition, the excess conductivity analyses based on the theory of Aslamazov - Larkin (AL) and Lawrence - Doniach (LD) showed decreases in the coherence lengths (ξ c (0)) from 1.957 Å to 1.565 Å and the effective inter-layering spacing (d) from 79.7 Å to 64.5 Å. Meanwhile, the interlayer coupling strength (J) between two CuO 2 planes was estimated to increase from 0.00083 to 0.00137. These results might be evidence to conclude that the increasing of the sintering temperature obviously improves the superconductivity in the BPSCCO system.